Blood Biomarkers of Glioma in Response Assessment Including Pseudoprogression and Other Treatment Effects: A Systematic Review - Raza, Istafa J.; Tingate, Campbell A.; Gkolia, Panagiota; Romero, Lorena; Tee, Jin W.; Hunn, Martin K. (Frontiers in Oncology, 2020)
Imaging-based monitoring of disease burden in glioma patients is frequently confounded by treatment effects. Circulating biomarkers could theoretically augment imaging-based response monitoring. This systematic review aimed to present and evaluate evidence for differential expression and diagnostic accuracy of circulating biomarkers with respect to outcomes of tumor response, progression, stable disease and treatment effects (pseudoprogression, radionecrosis, pseudoresponse and pseudo-lesions) in patients undergoing treatment for WHO grades II-IV diffuse astrocytic and oligodendroglial tumors. MEDLINE, EMBASE, Web Of Science and SCOPUS databases were searched until 18th August 2019 for observational or diagnostic studies on multiple circulating biomarker types: extracellular vesicles, circulating nucleic acids, circulating tumor cells, circulating proteins and metabolites, angiogenesis related cells, immune cells and other cell lines. Methodological quality of included studies was assessed using an adapted QUADAS-2 tool, and level of evidence (IA-IVD) for individual biomarkers was evaluated using an adapted framework from the National Comprehensive Cancer Network guidelines on evaluating tumor marker utility. Out of 13,202 unique records, 58 studies met inclusion criteria. 133 distinct biomarkers were identified in a total of 1853 patients across various treatment modalities. Fifteen markers for response, progression or stable disease, and 5 markers for pseudoprogression or radionecrosis reached level IB. No biomarkers reached level IA. Only five studies contained data for diagnostic accuracy measures. Overall methodological quality of included studies was low. Whilst extensive data on biomarker dysregulation in varying response categories was reported, no biomarkers with clinical applicability were identified. Further assay refinement and evaluation in larger cohorts with diagnostic accuracy study designs is required.